Penerapan Media Augmented Reality (AR) untuk Meningkatkan Minat dan Hasil Belajar Matematika Siswa pada Materi Bangun Ruang - Andriawan, Wawan (Media Pendidikan Matematika, 2024)
This study aims to improve students' interest and learning outcomes in mathematics by using Augmented Reality media. The research is a classroom action study conducted in two cycles. Each cycle consists of four stages: planning, implementation, observation, and reflection. The subjects of this study were 26 students of class VII.2 at SMPN Satap 2 Bayan. Based on the research conducted, it was found that the application of learning media using Augmented Reality can enhance students' interest and learning outcomes in the topic of solid geometry. In the first cycle, students' learning interest reached 62%, and learning outcomes were at 27%. In the second cycle, there was an increase, with learning interest rising to 84% and learning outcomes improving to 88%. This demonstrates that the implementation of learning media using Augmented Reality effectively enhances students' interest and learning outcomes in the topic of solid geometry.